Dyeing of ramie yarn with Reactive Blue 19 in liquid ammonia. Issue 2 (December 2016) - Cai, Yingjie; Wen, Shu; Yuan, Chi; Liu, Fan; He, Linwei; Lin, Lina
Abstract : Liquid ammonia dyeing is an anhydrous dyeing process that uses liquid ammonia instead of water. There are reports that the liquid ammonia dyeing performance is unsatisfactory due to problems of low exhaustion and poor fixation. In this work, ramie yarn was cationically modified using 2, 3-epoxypropytrimethylammonium chloride. The original and cationic yarns were dyed with Reactive Blue 19 in liquid ammonia. The dyeing time varied from 10 to 600 s with 10% dye on mass of fiber (OMF), and the dye mass ranged from 1 to 100% dye OMF for 600 s at −35°C at a liquor-to-goods ratio of 1:35. After dyeing, the dyed samples were dried at 100°C for 10 min, followed by a soaping-off treatment. The results indicated that the dyeing equilibrium time for the original ramie yarn was 60 s and that for the cationic yarn was 300 s. Thus, the cationic treatment improved both dye exhaustion and fixation.